Accounting Students' Perceptions of a Career as a Public Accountant: Job Market Considerations, Work Environment, Workload, and Financial Rewards - Anjani, Amanda Putri Dwi; Herawansyah, Herawansyah; Baihaqi, Baihaqi (CV. Proaksara Global Transeduka, 2025)
The Indonesian Institute of Public Accountants (IAPI) reports that there is a significant lack of personnel in the field of public accounting. This is reflected in the accounting profession's key role in instilling professional principles, integrity, and competence that are not only intelligent in calculations but also must understand the economic situation at large and can present an assessment in the form of information that can be used for decision-making. This scenario highlights the importance of students in addressing the growing demand for public accountants in Indonesia. The primary objective of this research is to identify discrepancies in past studies on how job market factors, work environment, workload, and financial incentives shape accounting students' perception of a career as public accountants. The methodology employed in this study involves a quantitative strategy, and the target population consists of PTN registered in the LLDIKTI region of Region II. Based on the results of this study, it is known that the implications of variables of consideration of the job market, work environment, workload, and financial rewards support the theory of planned behavior, and it is important for students to consider and know how their perception of a profession is, such as the possibility of getting a job in that career, the circumstances and conditions of the workplace environment they will encounter, the pressure of the work done, and the reward or salary to be received. Future research can enhance this model by adding moderation variables and expanding the sample for more accurate results.